2021
DOI: 10.3390/biom11020317
|View full text |Cite
|
Sign up to set email alerts
|

Silver Nanoparticles Induce Neutrophil Extracellular Traps Via Activation of PAD and Neutrophil Elastase

Abstract: Silver nanoparticles (AgNPs) are widely used in various fields because of their antimicrobial properties. However, many studies have reported that AgNPs can be harmful to both microorganisms and humans. Reactive oxygen species (ROS) are a key factor of cytotoxicity of AgNPs in mammalian cells and an important factor in the immune reaction of neutrophils. The immune reactions of neutrophils include the expulsion of webs of DNA surrounded by histones and granular proteins. These webs of DNA are termed neutrophil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…However, many studies have reported that AgNPs can be harmful to both microorganisms and humans. The authors showed that 5 nm AgNPS caused NET release, but 100 nm AgNPs did not [ 14 ]. For SeNPs, the dependence of their efficiency on size was also shown [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, many studies have reported that AgNPs can be harmful to both microorganisms and humans. The authors showed that 5 nm AgNPS caused NET release, but 100 nm AgNPs did not [ 14 ]. For SeNPs, the dependence of their efficiency on size was also shown [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the undeniable “positive” role of the neutrophil in the body, researchers have identified a range of pathological conditions, including autoimmunity and cancer, when neutrophil activity can be harmful to the body [ 11 , 12 ]. Thus, uncontrolled cytotoxic activity, excessive formation of ROS, and NETs can initiate tissue damage that can cause chronic inflammation and autoimmune disease [ 11 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Little is known about how nanomaterials impact NETosis, much less whether specifically metal oxide NPs and GBCAs enhance NETosis. How the physiochemical attributes of NPs modulate neutrophil behavior has been studied in gold, silver, and iron oxide NPs [ 76 , 77 , 78 , 79 , 80 ]. Manganese oxide NPs have not been studied specifically in regards to NETosis, but inhaled Mn 3 O 4 is known to cause respiratory inflammation; in fact, one study found that Mn 3 O 4 induced increases of oxidative stress in human alveolar macrophages of up to 700%, as well as more modest increases in oxidative stress in human airway epithelial cells [ 81 ].…”
Section: Introductionmentioning
confidence: 99%
“…The capacity of NPs to cause NETosis has also been investigated in silver NPs (AgNPs), particularly in the context of whether AgNP size or concentration influences NET formation [ 77 , 79 , 80 ]. Human neutrophils were exposed to 5 nm AgNPs and 100 nm AgNPs at varying concentrations of 0 µg/mL to 2 µg/mL for 4 h. Starting at a concentration of 1.2 µg/mL, the 5 nm AgNPs induced significant NETosis which increased with higher NP concentrations; however, the 100 nm AgNPs did not induce NETosis regardless of concentration [ 77 ]. Another study reported that 15 nm AgNPs induced neutrophil necrosis, increased oxidative stress, and facilitated the release of interleukin-1β, which itself can stimulate further NETosis and enhance neutrophil recruitment [ 79 , 80 , 84 ].…”
Section: Introductionmentioning
confidence: 99%
“…NETs allow neutrophils to catch and destroy pathogens in extracellular spaces. Kang et al [ 5 ] investigated how AgNPs stimulate neutrophils, specifically focusing on NETs. They found that AgNP induced NETs through ROS, peptidyl arginine deiminase, and neutrophil elastase.…”
mentioning
confidence: 99%